PERCEPTIONS OF MRSM ENGLISH TEACHERS ON PROFESSIONAL DEVELOPMENT AND THEIR EXPECTATIONS ON IN-SERVICE TRAINING - Faizahani Ab Rahman; Nurul Afrahah Hussin; Sutha A/P Sugumaran, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This paper looks at the perceptions of MRSM (Majlis Amanah Rakyat or also known as People’s Trust Council) English teachers on their current professional development and their expectations on in-service training. As teachers, they are often expected to act as a source of motivation to their students apart from being accountable in providing instructions, knowledge, and skills in their respective academic subjects. However, very often, teachers are not provided with sufficient and appropriate training that would prepare them to be the kind of teacher that they are required and expected to be. This prompts this study that determines whether the in-service training provided is sufficient and aptly to help the teachers produce academically excellent students. This case study used a qualitative approach with purposive sampling of seven English teachers at Maktab Rendah Sains MARA, Beseri in Perlis with teaching experiences between 10 to 30 years. Semi-structured interviews and focus group methods were used to answer the research question which dwells on the MRSM English teachers’ expectations of professional development teacher training of their students’ achievement. The findings of the study revealed that teachers expect to have more professional development in terms of pedagogy, proficiency level, technology integration, and stress management. They also believe that improvement in professional development can positively affect their students’ achievement as teaching and learning processes can be done more effectively. It is therefore recommended that MARA should highlight its current in-service training and development policy to be consistent with the needs of teachers.